Implementation of a hierarchical Production planning system in a Ceramic Tiles manufacturing company - Çelik, Behzat Hakan (My University, 1996)
unknown
Keywords: Genel yönetim; Üretim yönetimi; ÜRETİM YÖNETİMİ